The Potential of Exosomal RNAs in Atherosclerosis Diagnosis and Therapy - Yang, Wenzhi; Pan, Xudong; Ma, Aijun (Frontiers in Neurology, 2021)
Exosomal RNAs have great potential in disease diagnosis and therapy. Atherosclerosis is a inflammatory diseases which can lead to stroke, which is associated with dysfunction of endothelial cells and macrophages. In atherosclerosis (AS) micro-environment, exosomes secreted from various cells, especially the macrophages-derived exosomes, play an important role in cells-cells communication, and regulate the AS process. In this paper we review the previous researches about exomal RNAs, and discuss the potential value in AS diagnosis and therapy.